Raw data from: Does green manuring positively affect the soil macro-invertebrates in vineyards? A case study from Kaltern/ Caldaro (South Tyrol, Italy) - Michael Steinwandter; Florian Haas; Gregor Degasperi; Manfred Kahlen; Alexander Rief; Verena Ostermann; Julia Seeber (PANGAEA, 2019)
In the last decades, low permanent cover crops were established in vineyard alleyways to facilitate management. However, a consequence was the decline of flora and fauna diversity. Green manuring by seeding flowering plants and mulching them into the soil represents an alternative. Here we hypothesize that green manuring positively affects the soil macro-invertebrate communities. The vineyard alleyways were managed with following four treatments: permanent cover crop (PCC) and green manuring as control (GMC), as well as activated (cow horn manure, GMA), and with slurry (GMS). Soil macro-invertebrates were obtained from pitfall traps and soil core samples. Additionally, 11 soil properties were measured. The treatments differ only in two soil properties (i.e. potassium and ammonia). However, we found significant differences in the soil macro-invertebrate communities, with GM treatments harbouring more rare and unique Araneae and Coleoptera species which represent 45.07 % of all taxa (vs. 18.75 % in PCC). Here we present one of few existing studies investigating soil macro-invertebrates in vineyards. We were able to record and confirm rare Araneae and Coleoptera species, with two new Coleoptera species records for South Tyrol. Green manuring seems to considerably increase the biodiversity of ground-living invertebrates, and even facilitates the preservation of soil fertility. Finally, we assume that a certain amount of plant-associated species such as phytophagous Coleoptera was not covered by our sampling methods.
Supplement to: Steinwandter, M et al. (2018): Does green manuring positively affect the soil macro-invertebrates in vineyards? A case study from Kaltern/Caldaro (South Tyrol, Italy). Gredleriana, 18, https://www.zobodat.at/pdf/Gredleriana_018_0017-0025.pdf